A kind of special weld lines with high specific strength and elongation obtained by core-back chemical foam injection molding - H. Wu; G. Zhao; J. Wang; G. Wang; M. Zhang (eXPRESS Polymer Letters)
In this paper, a kind of polypropylene (PP) foam plastic parts with special weld lines were obtained by core-back foam injection molding with chemical blowing agent. A new kind of weld line was found and its formation process was proposed. The unique principle of the weld lines formation in core-back foam injection molding process was revealed. The surface and internal morphologies, fracture morphologies, cell structure, and mechanical properties of the weld line area of the specimens respectively obtained by core-back foam injection molding and conventional foam injection molding were compared and analyzed. The mechanism of core-back foam injection molding in improving the mechanical properties of the weld line was clarified. The results show that the specimens with special weld lines not only have relatively uniform inner cell structure in size and distribution, but also have a special reticular structure in the weld line area. This reticular structure can not only play a role similar to fiber reinforcement itself, but also increases the bonding degree of polymer at weld lines. Under the action of this special weld line structure, the tensile strength and elongation at break of the specimen are significantly improved, and the weight reduction effect is much better under the premise of ensuring certain mechanical properties.